A Neuroscientific Perspective on the Therapeutic Alliance and How Talking Changes the Brain: Supporting a Common Factors Model of Psychotherapy - Nicole Hess (Psychotherapy and Counselling Journal of Australia)
For decades, the efficacy and application of psychotherapeutic treatments has been informed and driven by a medical model of understanding. Within this framework, for a psychotherapeutic treatment to be classified as "empirically supported," the therapeutic intervention alone must be demonstrated to be the mechanism responsible for change. With 85% of the psychotherapeutic outcome accounted for by non-specific factors (that do not include the type of therapy engaged in) this framework of understanding is seriously problematic and undermines the evidence-based efficacy of most psychotherapies. Research clearly identifies that interpersonal factors, including the therapeutic alliance, are robust predictors of successful outcomes in therapy and these findings are further supported by neuroscientific evidence. The current paper describes the neuro-correlates of psychotherapy and how these are operationalised through talking and the therapeutic alliance. Recommendations are presented in support of an integrative approach to psychotherapy that is guided by person-centred, idiographic considerations, yet underpinned by neuroscientific and evidence-based treatment protocols.